Stress and Coping in Adolescents - Allen, Sandra; Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2011)
Two hundred and eighty-five grade 10, 11 and 12 students were surveyed regarding the types of demands they faced, how well they thought they coped with those demands, and the level of stress they experienced in those situations. The students were also asked about their general anxiety level, prevalence of stress-related symptoms, and general coping facility. The results suggest that adolescents with greater coping resources demonstrated lower levels of stress and less frequent stress symptoms. Furthermore, stress levels in adolescents are higher and their coping resources are more meagre than the population at large. Differences in stress levels and coping adequacy for gender and other demographic variables were also noted.